The Digital Cost of Revenue Recording System at PT. Alam Mulya - Ratna Dwi Budi Rahmawati; Sri Trisnaningsih (International Journal of Economics and Management Sciences, 2025)
This research aims to examine and describe the implementation of a digital-based Cost of Revenue recording system at PT Alam Mulya as a logistics service company. Amid the rapid development of information technology, digital-based financial recording systems have become a strategic solution for enhancing efficiency, accuracy, and transparency in financial reporting. This study employs a qualitative descriptive approach, utilizing data collection techniques through literature review, direct observation, and interviews with parties involved in the company's financial recording process. The research findings indicate that the use of the Shortcut-AM application can accelerate the real-time recording of direct costs, reduce the risk of recording errors, and facilitate internal monitoring and audits. However, the effectiveness of the system still faces several challenges, such as delays in collecting supporting documents, account classification errors, and discrepancies between account mutation data and internal records. These challenges highlight the importance of cross-divisional coordination, ongoing technical training, and strengthening internal controls to ensure the system operates optimally. Thus, the digital-based recording system not only enhances operational efficiency but also serves as an essential foundation for maintaining the integrity and accountability of the company's financial reports.